The Application of Youtube Teaching Media in Writing Skills - Lumban Raja, Theodora Evita Bella; Napitupulu, Selviana (Innovative: Journal Of Social Science Research, 2025)
This article explores the application of YouTube as a teaching medium to enhance writing skills among students. In the context of the digital age and the increasing importance of multimedia in education, YouTube has emerged as a potentially powerful tool for language instruction, particularly in developing writing proficiency. This study examines how YouTube can be effectively integrated into writing instruction to improve various aspects of writing, including vocabulary, grammar, structure, and creativity. The research considers the challenges and benefits of using YouTube in the classroom, as well as strategies for its effective implementation. By analyzing current practices and emerging trends, this study aims to provide insights into how educators can leverage YouTube to create more dynamic, engaging, and effective writing instruction. The findings suggest that when used thoughtfully and strategically, YouTube can significantly enhance students' writing skills, motivation, and overall engagement with the writing process.